Assessing Shared Decision‐Making Clinical Behaviors Among Genetic Counsellors. Issue 1 (21st December 2018) - Birch, Patricia H.; Adam, S.; Coe, R. R.; Port, A. V.; Vortel, M.; Friedman, J. M.; Légaré, F.
Abstract: Shared decision‐making (SDM) is a collaborative approach in which clinicians educate, support, and guide patients as they make informed, value‐congruent decisions. SDM improves patients' health‐related outcomes through increasing knowledge, reducing decisional conflict, and enhancing experience of care. We measured SDM in genetic counselling appointments with 27 pregnant women who were at increased risk to have a baby with a genetic abnormality. The eight experienced genetic counsellors who participated had no specific SDM training and were unaware that SDM was being assessed. Audio transcripts of appointments were scored using 'Observing Patient Involvement in Decision Making' (OPTION 12 ). Patients' anxiety and decisional conflict were also assessed. The genetic counsellors' mean OPTION 12 score was 42.4% (SD 9.0%; possible range 0–100%). Specific SDM behaviours that scored highest included introducing the concept of equipoise and listing all options with their pros and cons. Behaviours that scored lowest included eliciting patients' preferred approach to receiving information and desired degree of involvement in decision‐making. Patients' levels of anxiety and decisional conflict were unassociated with genetic counsellors' OPTION 12 scores. Some SDM behaviours were better demonstrated in this prenatal genetic counselling study than others. Formal training of genetic counsellors in SDM may enhance use of this approach in their professional practice.